Investigation of electrode processes in proton exchange membrane fuels cells : a self-assembly approach - Liu, Zengcai (2008)
The polymer stabilized Pt nanoparticles were synthesized via alcohol reduction in the presence of polymers, PDDA, PVP, PSS and Nafion. PDDA-Pt nanoparticles show high catalytic activity for the oxygen reduction reaction in the absence and presence of methanol, but low catalytic activity for methanol oxidation reaction. PSS-Pt nanoparticles are catalytically very active for both oxygen reduction and methanol oxidation reactions. Thus, PSS-Pt nanoparticles show very low activity for oxygen reduction in the presence of methanol due to the direct chemical reaction between the oxygen and methanol. These results show that different polymers may exhibit different selectivity to Pt nanoparticles As-synthesized PDDA-Pt nanoparticles can be self-assembled on the Nafion membrane due to the electrostatic interaction between positively charged PDDA-Pt nanoparticle and negatively charged SO3- on the surface of Nafion membrane. The results shows that modified Nafion membrane reduced the methanol crossover, and the cell performance increased by about 34% compared to that using the unmodified Nafion membrane. Self-assembled multilayer of PDDA/PSS on Nafion membrane was also found to reduce the methanol crossover effectively, and the cell performance was increased by 39% compared with the unmodified Nafion membrane.